1998
DOI: 10.1143/jjap.37.4806
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of a Nuclear Pumped 3He–Ne–Ar Gas Laser for its Optimization

Abstract: The numerical simulation of a nuclear pumped 3He–Ne–Ar gas laser (λ=585.3 nm) has been made to estimate the optimal gas mixtures. The calculation shows that the optimization is established under a condition of He pressure of 2280 Torr, Ne pressure of 24 Torr, and Ar pressure of 8 Torr. The oscillation is expected to occur at a thermal neutron flux density of 3.3×1014 cm-2 s-1 when the cavity length is 50 cm and the mirror reflection coefficient is 99%. On the other hands, the energy efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…The rate of gas ionisation ( ≈10 16 cm −3 s −1 ) was evaluated based on known cross-sections of nuclear reactions and the ranges of protons and tritons in gas. The correlation between (20) and the experimentally observed dependence (see Figure 3) yields ∞ ≈200 units and ∼ 10 −13 cm 3 s −1 .…”
Section: Emission Of 3 He-xe-cd Mixturessupporting
confidence: 52%
See 1 more Smart Citation
“…The rate of gas ionisation ( ≈10 16 cm −3 s −1 ) was evaluated based on known cross-sections of nuclear reactions and the ranges of protons and tritons in gas. The correlation between (20) and the experimentally observed dependence (see Figure 3) yields ∞ ≈200 units and ∼ 10 −13 cm 3 s −1 .…”
Section: Emission Of 3 He-xe-cd Mixturessupporting
confidence: 52%
“…The lasing threshold was not achieved. Further theoretical research [19,20] and experiments conducted by other organisations [21][22][23] indicated that the lasing threshold for the line at 585 nm exceeds 10 14 n/cm 2 s. The processes involved in the active media of lasers at the 3p-3s transitions of NeI are considered to be well studied [19,24]: the population of the upper laser level occurs primarily because of the dissociative recombination of Ne 2 + and HeNe + molecular ions. Under relatively weak pumping, HeNe + ions also form Ne 2 + ions through the following substitution reaction:…”
Section: Mechanisms Of Populating the P Levels Of Inert Gasmentioning
confidence: 99%